PENGARUH DIGITAL LEARNING AND DIGITAL GAMES TRAINING TERHADAP KOMPETENSI TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE GURU SMA - Putra, Alfyananda Kurnia; Sumarmi, Sumarmi; Handoyo, Budi; Fajrilia, Azni; Islam, Muhammad Naufal; Attamimi, Muhammad Rafi (Universitas Negeri Malang, 2022)
(EFFECTS OF DIGITAL LEARNING AND DIGITAL GAMES TRAINING ON THE SENIOR HIGH SCHOOL TEACHERS' TECHNOLOGICAL PEDAGOGY CONTENT KNOWLEDGE SKILLS) The development of digital technology requires teachers to present a sustainable learning process without the limitations of space and time. The presentation of digital learning provides opportunities for students to prepare for work competencies in the 21st Century and provides learning experiences that generate enthusiasm and a positive learning environment for students. This study aims to reveal the effect of digital learning and digital games in education training on the technological pedagogical content knowledge of teachers at SMAN Kepanjen Malang Regency. This type of research is experimental research packaged in a training program with pretest and posttest to measure the competence of TPACK teachers. The implementation method is carried out in stages, namely (1) needs and situation analysis, (2) program socialization and training implementation, (3) evaluation. The research subjects were SMAN 1 Kepanjen teachers with different scientific backgrounds. The analysis in this study used the N-gain score test, which was carried out by calculating the difference between the pretest and posttest scores. The training facilities use gamification media and the Learning Management System (LMS). The results of this training influence knowledge, competence, and capability related to technological pedagogical content knowledge. This is because teachers are getting used to and taking advantage of modern features in the LMS, namely user management, course management, forums, lessons, big blue buttons, and others. Perkembangan teknologi digital menuntut guru untuk menghadirkan proses pembelajaran yang berkelanjutan tanpa batasan ruang dan waktu. Penyajian pembelajaran digital memberikan kesempatan kepada siswa untuk mempersiapkan kompetensi kerja di abad 21 dan memberikan pengalaman belajar yang membangkitkan semangat dan lingkungan belajar yang positif bagi siswa. Penelitian ini bertujuan untuk mengungkapkan pengaruh pembelajaran digital dan permainan digital dalam pelatihan pendidikan terhadap pengetahuan konten pedagogik teknologi guru di SMAN Kepanjen Kabupaten Malang. Jenis penelitian ini adalah penelitian eksperimen yang dikemas dalam program pelatihan dengan pretest dan postest untuk mengukur kompetensi guru TPACK. Metode pelaksanaan dilakukan secara bertahap, yaitu (1) analisis kebutuhan dan situasi, (2) sosialisasi program dan pelaksanaan pelatihan, (3) evaluasi. Subjek penelitian adalah guru SMAN 1 Kepanjen dengan latar belakang keilmuan yang berbeda. Analisis dalam penelitian ini menggunakan tes skor N-gain yang dilakukan dengan menghitung selisih skor pretest dan postest. Fasilitas pelatihan menggunakan media gamifikasi dan Learning Management System (LMS). Hasil pelatihan ini mempengaruhi pengetahuan, kompetensi, dan kapabilitas terkait dengan technological pedagogical content knowledge. Hal ini karena para guru mulai terbiasa dan memanfaatkan fitur-fitur modern di LMS, yaitu manajemen pengguna, manajemen kursus, forum, pelajaran, tombol biru besar, dan lain-lain.